(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
A 2-yrs study was carried out on deaths allegedly due to hanging and strangulation at Govt. Medical College, Amritsar. Out of total 43 cases, on autopsy, 25(58.1%) were due to hanging and 18(41.9%) were due to strangulation. Majority of victims of both hanging (48%) and strangulation (38.7%) were in 21-30 yrs age group having urban preponderance (83.3%). Approximately 2/3rd of hanging victims were males as compared to females. Majority of victims comprised of urban population (56%) however rural males were ones predominantly involved (40%). Married victims were double the numbers in comparison to unmarried victims; in known cases (84%). In 76% hanging cases no associated trauma was present other than the ligature mark. Rope was used as ligature material in the majority (44.1%) and the ligature was placed above the level of thyroid cartilage in 88% of cases.